2011
DOI: 10.1002/hep.24362
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 15 activates hepatitis B virus gene expression and replication

Abstract: Hepatitis B virus (HBV) is a small DNA virus that requires cellular transcription factors for the expression of its genes. To understand the molecular mechanisms that regulate HBV gene expression, we conducted a yeast one-hybrid screen to identify novel cellular transcription factors that may control HBV gene expression. Here we demonstrate that Krüpple-like factor 15 (KLF15), a liver-enriched transcription factor, can robustly activate HBV surface and core promoters. Mutations in the putative KLF15 binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…KLFs are expressed in multiple tissues and regulate the expression of genes involved in glucose uptake and adipogenesis [31], [32]. KLF3 is an important regulator of several biological processes, including adipogenesis, erythropoiesis, and B cell development [33]; while, KLF15 was proposed for the regulation of the HBV gene expression and replication [34]. The role of KLF15 on HBV replication was confirmed by our experimental data.…”
Section: Discussionsupporting
confidence: 71%
“…KLFs are expressed in multiple tissues and regulate the expression of genes involved in glucose uptake and adipogenesis [31], [32]. KLF3 is an important regulator of several biological processes, including adipogenesis, erythropoiesis, and B cell development [33]; while, KLF15 was proposed for the regulation of the HBV gene expression and replication [34]. The role of KLF15 on HBV replication was confirmed by our experimental data.…”
Section: Discussionsupporting
confidence: 71%
“…9B) and Krüpple-like factor 15 (KLF15). A recent report demonstrated that RNA interference (RNAi) knockdown of KLF15 in vitro and in vivo significantly reduced core promoter activity and core protein expression, respectively (47). It has also been reported that mutating the Sp1-1 binding site significantly reduced precore RNA (pcRNA)/pgRNA levels, which were further reduced with additional mutation of the Sp1-2 site (21).…”
Section: Vol 85 2011 Multiple Effects Of 36-nt Insertion Of Hbv Genmentioning
confidence: 99%
“…Potential binding sites could be predicted for four cellular factors: glial cells missing homolog 1, heat shock factor 1, Kruppel-like factor (KLF15), and sterol regulatory element binding protein. Among these factors, KLF15 has been shown to activate the SP2 promoter of HBV in a previous study, but the precise binding site of KLF15 has not been defined (29). Therefore, it will be interesting to investigate whether KLF15 binds to this region and whether HNF6 can suppress the KLF15-mediated SP2 activation in future work.…”
Section: Discussionmentioning
confidence: 99%